RESISTANCE OF COLLECTION SAMPLES OF WINTER WHEAT TO LEAF DISEASES IN THE CONDITIONS OF ROSTOV REGION - T. G. Derova; N. V. Shishkin; Т. А. Grichanikova1; N. P. Voytsutskaya (Зерновое хозяйство России)
116 cultivars of winter wheat of different ecological-geographical origin were analyzed on resistance to leaf rust  (Puccinia triticina Erikss) and powdery mildew (Erysiphe graminis D.C.). These pathogens are the most spread and harmful in Rostov region. The infected plants decrease their productivity on 10-15%, sometimes even on 30%. Cultivars 75/481, Zolotokolosa, Pyvna (Ukraine) and KS 93 U 50 (US) which possess the highest resistance to leaf rust have been selected on the artificially infected allotment. Cultivars IL84-3132-1, KS 93 U 11 (US) and Zrazkova (Ukraine) turned to be the most resistant cultivars (infected on 10-25%). Cultivars KS 96 Wg RC 34 (US), Webster (Canada), Dobirna and Spivanka (Ukraine) turned to be less resistant. The rest cultivars were infected most of all, up to 40% and in some years up to 80-100%.  During analyzing the study of winter wheat resistance to leaf rust we found 15 cultivars totally resistant to infection, among which Fokus, Derby, Gaspard (France), Banga (Latvia) and others. Due to long-term study we could select cultivars with a group resistance to leaf rust and powdery mildew. The study results can be used for cultivation of new varieties resistant to fungus diseases.